2007
DOI: 10.1111/j.1532-7078.2007.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mouthing on Infant Vocalization

Abstract: Although vocalization and mouthing are behaviors frequently performed by infants, little is known about the characteristics of vocalizations that occur with objects, hands, or fingers in infants' mouths. The purpose of this research was to investigate characteristics of vocalizations associated with mouthing in 6-to 9-month-old infants during play with a primary caregiver. Results suggest that mouthing may influence the phonetic characteristics of vocalizations by introducing vocal tract closure and variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…The production of CV syllables is perhaps the most important language milestone of the first year, and delayed emergence of CV syllables is a reliable predictor of later language delay (Oller et al, 1998). Fagan and Iverson (2007) found that relative to vocalizations unaccompanied by object mouthing, vocalizations produced while infants were mouthing objects were more likely to contain a CV syllable and to contain a greater variety of consonant sounds. They suggested that object mouthing provided infants with opportunities to explore vocal production when the vocal tract was partially blocked (as it is during consonant production).…”
Section: Discussionmentioning
confidence: 88%
“…The production of CV syllables is perhaps the most important language milestone of the first year, and delayed emergence of CV syllables is a reliable predictor of later language delay (Oller et al, 1998). Fagan and Iverson (2007) found that relative to vocalizations unaccompanied by object mouthing, vocalizations produced while infants were mouthing objects were more likely to contain a CV syllable and to contain a greater variety of consonant sounds. They suggested that object mouthing provided infants with opportunities to explore vocal production when the vocal tract was partially blocked (as it is during consonant production).…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, object exploration abilities are directly related to the development of cognitive skills such as object knowledge (Caruso, 1993; Bourgeois et al, 2005), non-verbal, and verbal communication skills such as the use of gestures and words within a social context (Fagan and Iverson, 2007; Iverson and Wozniak, 2007), as well as social skills such as imitation, joint attention, and pretend play (Bruckner and Yoder, 2007; McDuffie et al, 2012). Promoting object interactions within a social context will enhance multisystem development of infants at-risk for developing ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact three weeks of enhanced postural training led to improved reaching, mouthing, and fingering of objects in 2- to 5-month-old TD infants (Lobo and Galloway, 2008). Moreover, object exploration skills have implications for other forms of development such as perceptual (Needham, 2000; Bhat and Galloway, 2006; Lobo and Galloway, 2008; Koterba et al, 2012), social communication (Meltzoff, 1995; Fagan and Iverson, 2007; Iverson et al, 2007), and cognitive development (Caruso, 1993; Bourgeois et al, 2005; Fontenelle et al, 2007). In terms of perceptual development, infants learn various object properties such as texture, shape, size, color, and sound while exploring objects (Ruff, 1984, 1986; Palmer, 1989; Rochat, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that 6–9-month-olds produce more frequent and more varied supra-glottal consonants (i.e., made with lips or tongue) during play interactions with their primary caregiver, if they vocalize while mouthing an object or their fingers/hand (contact with mouth, lips or tongue) than if they are not mouthing an object. The authors concluded that active oral engagement with objects introduces and enhances variations in vocal tract closures (i.e., consonantal gestures) during social play vocalizations, due to the increased multimodal information provided by mouthing and vocalizing simultaneously, which encourages exploration of consonant production (Fagan & Iverson, 2007). This interpretation may extend to understanding the bias toward posterior consonant imitation by younger infants.…”
Section: Converging Evidence For Articulatory-based Attunement Of Permentioning
confidence: 99%